2011
DOI: 10.1039/c0ob01148g
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl radical addition reaction through the homolytic cleavage of a benzylic C–H bond

Abstract: Direct generation of a benzyl radical by C-H bond activation of toluenes and the addition reaction of the resulting radical to an electron deficient olefin were developed. The reaction of dimethyl fumarate with toluene in the presence of Et(3)B as a radical initiator at reflux afforded 2-benzylsuccinic acid dimethyl ester in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…To validate our proposal, we studied the Giese-type radical conjugate addition 22 to dimethyl fumarate 3a (Fig. 2b) [23][24][25][26] . The experiments were conducted in acetonitrile (CH3CN) using commercially available γ-terpinene as a cheaper and more stable surrogate of 1,4-CHD.…”
mentioning
confidence: 86%
“…To validate our proposal, we studied the Giese-type radical conjugate addition 22 to dimethyl fumarate 3a (Fig. 2b) [23][24][25][26] . The experiments were conducted in acetonitrile (CH3CN) using commercially available γ-terpinene as a cheaper and more stable surrogate of 1,4-CHD.…”
mentioning
confidence: 86%
“…Watson and co‐workers reported that Cu(I) catalysts initiate radical reactions of nitroalkanes with benzyl bromides 10b. However, to the best of our knowledge, there are no examples of the direct substitution of benzyl alcohols instead of benzyl halides via benzyl radicals 12…”
Section: Introductionmentioning
confidence: 99%
“…Benzylation of olefins starting directly from alkylbenzenes has only a few precedents in the literature. As an example, Naito and co‐workers reported the radical benzylation of electron‐poor olefins by means of the Et 3 B/O 2 system at 180 °C 15. Quite common is the use of peroxides16,17 for the generation of the radical intermediate, generally in the presence of metal catalysts 17.…”
Section: Resultsmentioning
confidence: 99%